PERAN KANTOR URUSAN AGAMA DALAM MENGATASI PERNIKAHAN DI BAWAH UMUR DESA TANAH TENGNGA KECAMATAN PALAKKA KABUPATEN BONE - Rihwayana; Rusdi, Muhammad; Genda, Maming (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Underage marriage remains a complex social issue in Palakka District, Bone Regency, influenced by economic factors, cultural traditions, low levels of education, and limited public understanding of the negative impacts of early marriage. This study aims to describe and analyze the role of the Office of Religious Affairs (Kantor Urusan Agama/KUA) of Palakka District in addressing underage marriage practices. The study employed a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The findings indicate that the KUA plays a strategic role in preventing early marriage through three main functions: educational, preventive, and coordinative. The educational function is implemented through community socialization regarding the legal minimum age of marriage in accordance with Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 on Marriage, while the preventive function is carried out by rejecting marriage registration applications that do not meet legal age requirements. The coordinative function is realized through collaboration with schools, community leaders, and related institutions to reduce the incidence of early marriage. However, the implementation of these roles still faces challenges, including strong local cultural influences, limited resources, and weak social supervision within the community. Therefore, the success of underage marriage prevention requires cross-sector collaboration and continuous improvement of public awareness.